Factors influencing post-graduation employment opportunities: A case study at a university in the Mekong Delta - Tran, Chuyen Trung; Tam, Nguyen Thi Thu; Khiem, Nguyen Tri (LPMPP Universitas Negeri Yogyakarta, 2026)
Employment remains one of the most urgent socio-economic issues, particularly in the context of ongoing economic fluctuations. Employment rates are also among the key targets of national macroeconomic development goals. This study aims to identify the factors influencing job adaptability in order to enhance students’ post-graduation employment opportunities. A mixed-methods approach was employed, incorporating expert consultation, analysis of industry reports, and a review of both domestic and international literature. In addition, a survey was conducted with 270 graduates from nine faculties at Nam Can Tho University (NCTU) who are currently working in the Mekong Delta region. The findings indicate that several factors significantly influence job adaptability and employment outcomes, including professional knowledge, soft skills, basic skills, academic performance, social networks, and work readiness. The results also reveal no significant gender differences in employment opportunities. However, variations are observed based on graduates’ hometowns, graduation cohorts, and academic rankings. Overall, this study contributes empirical evidence on key employability factors and provides practical insights for higher education institutions and policymakers to improve training quality and graduate employability.